A low-temperature lithium iron phosphate positive electrode material and preparation method thereof and battery
By adding modified zinc acetate and cerium oxide additives to the lithium iron phosphate cathode material, and combining inorganic carbon sources and organic carbon sources to form a carbon-coated conductive network, the electrochemical performance of LiFePO4 materials under low temperature conditions is solved. This problem is solved and the low-temperature performance of the material is significantly improved.
Patent Information
- Application Number
- CN202411463910.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-21
AI Technical Summary
LiFePO4 materials have poor electrochemical performance under low temperature conditions, mainly due to the slow diffusion rate of lithium ions and low electronic conductivity.
By binding the additives obtained from the modified treatment of zinc acetate and oxidation, the binding of lithium iron phosphate, and using the combination of inorganic carbon sources and organic carbon sources to form a carbon -covered conductive network in situ to optimize the spatial structure of the material.
It significantly improves the lithium-ion diffusion rate and electronic conductivity, improves the electrochemical properties of lithium iron phosphate orthopedic materials at low temperature. The discharge ratio capacity at 25 ℃ reaches 166mAh/G or more. More than 85%.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and more specifically, relates to a low-temperature lithium iron phosphate positive electrode material and a preparation method thereof and a battery. Background Art
[0002] LiFePO4 crystals have an ordered olivine structure and belong to the orthorhombic system. There are 4 LiFePO4 units in each unit cell. The interior of the LiFePO4 crystal is connected by FeO6 octahedrons and PO4 tetrahedrons in the form of shared edges, forming a stable skeleton structure. Lithium ions can be embedded and removed in the one-dimensional channel formed by the skeleton. The iron ions in the lattice are in a very stable polyanion skeleton structure. The charging and discharging process has little effect on the structural deformation. Therefore, lithium iron phosphate has good thermal stability. However, the ionic conductivity and electronic conductivity of LiFePO4 are both low, and during charging and discharging, Li + The diffusion channel between the two phases of LiFePO4-FePO4 is a one-dimensional channel. The low intrinsic conductivity and slow lithium ion diffusion rate lead to poor low-temperature performance of LiFePO4 materials. Shortening the lithium ion diffusion path, increasing the lithium ion diffusion rate, reducing the resistance of lithium ions during transfer and transmission, and improving the electron transfer path are currently widely used strategies to improve low-temperature performance. Summary of the invention
[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0004] In order to achieve these purposes and other advantages of the present invention, a method for preparing a low-temperature lithium iron phosphate positive electrode material is provided, comprising the following steps:
[0005] Step 1: Mix anhydrous iron phosphate, lithium carbonate and an organic carbon source, ball-mill, dry, and sinter for the first time to obtain a lithium iron phosphate precursor;
[0006] Step 2, adding ethylenediaminetetraacetic acid (EDTA) and ammonia water into deionized water, stirring evenly, then adding zinc acetate, cerium oxide and polyvinyl pyrrolidone, ultrasonically treating, concentrating and drying, grinding the obtained product and then heat-treating it to obtain an additive;
[0007] Step 3: The lithium iron phosphate precursor obtained in step 1 and the inorganic carbon source are mixed and ball-milled, and then the additive obtained in step 2 is added, and the ball-milling is continued, dried, and sintered for the second time to obtain a low-temperature lithium iron phosphate positive electrode material.
[0008] Preferably, in the step 1, anhydrous ferric phosphate and lithium carbonate are mixed in a molar ratio of Fe to Li of 1:1.0-1.2; and the mass ratio of the total mass of anhydrous ferric phosphate and lithium carbonate to the mass of the organic carbon source is 1:0.05-0.2.
[0009] Preferably, in step 1, the organic carbon source is one or more of glucose, sucrose, starch, cyclodextrin, polyethylene glycol, and polyvinyl alcohol; the process parameters of the first sintering are: temperature 400~700℃, heating rate 3~10℃ / min, and time 3~6h.
[0010] Preferably, in step 2, the molar ratio of ethylenediaminetetraacetic acid, NH3·H2O and zinc acetate is 1:4~6:0.5~1; the molar volume ratio of ethylenediaminetetraacetic acid and deionized water is 1 mol:0.7~1.5L; the mass ratio of zinc acetate, cerium oxide and polyvinylpyrrolidone is 1:1~3:0.1~0.3; and the concentration of ammonia water is 20wt%~30wt%.
[0011] Preferably, in step 2, the process parameters of ultrasonic treatment are: power 200~400W, frequency 50~70kHz, time 0.5~2h; the process parameters of heat treatment are: temperature 400~500℃, heating rate 10~30℃ / min, time 2~4h.
[0012] Preferably, in step 3, the mass ratio of the lithium iron phosphate precursor to the inorganic carbon source is 1:0.05-0.2; and the mass ratio of the additive to the lithium iron phosphate precursor is 0.005-0.02:1.
[0013] Preferably, in step three, the inorganic carbon source is one or more of carbon black, acetylene black, graphene, and carbon nanotubes; the process parameters of the second sintering are: temperature 500-800°C, heating rate 3-10°C / min, and time 4-8h.
[0014] Preferably, the specific conditions of the ball milling are: a rotation speed of 100-500 rpm, anhydrous ethanol as the ball milling medium, a solid-liquid ratio of 1:0.3-1, zirconia balls as the grinding balls, a ball-to-material ratio of 8-15:1, and a time of 2-6 hours.
[0015] A low-temperature lithium iron phosphate positive electrode material is prepared by the above-mentioned method for preparing the low-temperature lithium iron phosphate positive electrode material.
[0016] A battery, wherein the positive electrode material of the battery is the above-mentioned low-temperature lithium iron phosphate positive electrode material.
[0017] The present invention includes at least the following beneficial effects: the present invention uses zinc acetate and cerium oxide as raw materials, obtains additives through modification, and adds the additives to lithium iron phosphate, so as to better combine with lithium iron phosphate, optimize the spatial structure of lithium iron phosphate, increase the diffusion rate of lithium ions, increase the electronic conductivity, and effectively improve the electrochemical performance of lithium iron phosphate positive electrode materials at low temperatures; in addition, the present invention combines and optimizes the use of inorganic carbon sources and organic carbon sources, and the in-situ formed carbon-coated conductive network is beneficial to the improvement of the conductivity of the material, thereby preparing a low-temperature lithium iron phosphate positive electrode material with excellent low-temperature performance, and the discharge specific capacity thereof at 25°C and 0.2C reaches more than 166mAh / g, and the 0.2C discharge capacity retention rate at -20°C reaches more than 85%.
[0018] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0020] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0021] Example 1
[0022] A method for preparing a low-temperature lithium iron phosphate positive electrode material comprises the following steps:
[0023] Step 1, ball-mill anhydrous iron phosphate, lithium carbonate and glucose for 5 hours, transfer to a tube furnace after vacuum drying at 80°C, heat to 400°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep warm for 4 hours, and naturally cool to room temperature to obtain a lithium iron phosphate precursor; wherein the molar ratio of iron to lithium is 1:1.1, and the mass ratio of the total mass of anhydrous iron phosphate and lithium carbonate to glucose is 1:0.1; the specific conditions of ball milling are: the rotation speed is 300rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1;
[0024] Step 2: Add EDTA and 25wt% ammonia water to deionized water, stir evenly, then add zinc acetate, cerium oxide and polyvinyl pyrrolidone, perform ultrasonic treatment at 300W and 55kHz for 1h, evaporate and concentrate at 80℃ and then dry in vacuo at 100℃, grind the obtained dry product for 10min and transfer it to a tube furnace, heat it to 450℃ at a heating rate of 20℃ / min under a nitrogen atmosphere and keep it warm for 3h, and cool it naturally to room temperature to obtain an additive; wherein the molar ratio of EDTA, NH3·H2O and zinc acetate is 1:5:1, the molar volume ratio of EDTA and deionized water is 1mol:1L, and the mass ratio of zinc acetate, cerium oxide and polyvinyl pyrrolidone is 1:2:0.2;
[0025] Step 3, the lithium iron phosphate precursor and graphene obtained in step 1 are mixed in a mass ratio of 1:0.1 and ball-milled for 2 hours, then additives are added, and ball-milling is continued for 1 hour. After vacuum drying at 80°C, the mixture is transferred to a tubular furnace, and heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 6 hours, and naturally cooled to room temperature to obtain a low-temperature lithium iron phosphate positive electrode material; wherein the mass ratio of the additive to the lithium iron phosphate precursor is 0.01:1; the specific conditions for ball milling are: the rotation speed is 500rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1.
[0026] Example 2
[0027] A method for preparing a low-temperature lithium iron phosphate positive electrode material comprises the following steps:
[0028] Step 1, ball-mill anhydrous iron phosphate, lithium carbonate and polyethylene glycol 2000 for 5 hours, transfer to a tube furnace after vacuum drying at 80°C, heat to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep warm for 4 hours, and naturally cool to room temperature to obtain a lithium iron phosphate precursor; wherein the molar ratio of iron to lithium is 1:1.1, and the mass ratio of the total mass of anhydrous iron phosphate and lithium carbonate to polyethylene glycol 2000 is 1:0.05; the specific conditions of ball milling are: the rotation speed is 300rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1;
[0029] Step 2: Add EDTA and 25wt% ammonia water to deionized water, stir evenly, then add zinc acetate, cerium oxide and polyvinyl pyrrolidone, perform ultrasonic treatment at 300W and 55kHz for 1h, evaporate and concentrate at 80℃ and then dry in vacuo at 100℃, grind the obtained dry product for 10min and transfer it to a tube furnace, heat it to 450℃ at a heating rate of 20℃ / min under a nitrogen atmosphere and keep it warm for 3h, and cool it naturally to room temperature to obtain an additive; wherein the molar ratio of EDTA, NH3·H2O and zinc acetate is 1:5:1, the molar volume ratio of EDTA and deionized water is 1mol:1L, and the mass ratio of zinc acetate, cerium oxide and polyvinyl pyrrolidone is 1:2:0.2;
[0030] Step 3, the lithium iron phosphate precursor obtained in step 1 and acetylene black are mixed in a mass ratio of 1:0.15 and ball-milled for 2 hours, then additives are added, and ball-milling is continued for 1 hour. After vacuum drying at 80°C, the mixture is transferred to a tubular furnace, and heated to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 5 hours, and naturally cooled to room temperature to obtain a low-temperature lithium iron phosphate positive electrode material; wherein the mass ratio of the additive to the lithium iron phosphate precursor is 0.01:1; the specific conditions of ball milling are: the rotation speed is 500rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1.
[0031] Example 3
[0032] A method for preparing a low-temperature lithium iron phosphate positive electrode material comprises the following steps:
[0033] Step 1, ball-mill anhydrous iron phosphate, lithium carbonate and glucose for 5 hours, transfer to a tube furnace after vacuum drying at 80°C, heat to 400°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep warm for 4 hours, and naturally cool to room temperature to obtain a lithium iron phosphate precursor; wherein the molar ratio of iron to lithium is 1:1.1, and the mass ratio of the total mass of anhydrous iron phosphate and lithium carbonate to glucose is 1:0.1; the specific conditions of ball milling are: the rotation speed is 300rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1;
[0034] Step 2: Add EDTA and 25wt% ammonia water to deionized water, stir evenly, then add zinc acetate, cerium oxide and polyvinyl pyrrolidone, perform ultrasonic treatment at 300W and 55kHz for 1h, evaporate and concentrate at 80℃ and then dry in vacuo at 100℃, grind the obtained dry product for 10min and transfer it to a tube furnace, heat it to 450℃ at a heating rate of 20℃ / min under a nitrogen atmosphere and keep it warm for 3h, and cool it naturally to room temperature to obtain an additive; wherein the molar ratio of EDTA, NH3·H2O and zinc acetate is 1:5:1, the molar volume ratio of EDTA and deionized water is 1mol:1L, and the mass ratio of zinc acetate, cerium oxide and polyvinyl pyrrolidone is 1:1:0.2;
[0035] Step 3, the lithium iron phosphate precursor and graphene obtained in step 1 are mixed in a mass ratio of 1:0.1 and ball-milled for 2 hours, then additives are added, and ball-milling is continued for 1 hour. After vacuum drying at 80°C, the mixture is transferred to a tubular furnace, and heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 6 hours, and naturally cooled to room temperature to obtain a low-temperature lithium iron phosphate positive electrode material; wherein the mass ratio of the additive to the lithium iron phosphate precursor is 0.01:1; the specific conditions for ball milling are: the rotation speed is 500rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1.
[0036] Comparative Example 1
[0037] In this comparative example, glucose was not added, and the remaining steps were the same as those in Example 1.
[0038] Comparative Example 2
[0039] In this comparative example, graphene was not added, and the remaining steps were the same as those in Example 1.
[0040] Comparative Example 3
[0041] In this comparative example, zinc acetate and cerium oxide were directly added in the following manner:
[0042] Step 1, ball-mill anhydrous iron phosphate, lithium carbonate and glucose for 5 hours, transfer to a tube furnace after vacuum drying at 80°C, heat to 400°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep warm for 4 hours, and naturally cool to room temperature to obtain a lithium iron phosphate precursor; wherein the molar ratio of iron to lithium is 1:1.1, and the ratio of the total mass of anhydrous iron phosphate and lithium carbonate to the mass of glucose is 1:0.1; the specific conditions of ball milling are: the rotation speed is 300rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1;
[0043] Step 2: The lithium iron phosphate precursor obtained in step 1 and graphene are mixed in a mass ratio of 1:0.1 and ball-milled for 2 hours, and then zinc acetate and cerium oxide are added, and the ball milling is continued for 1 hour. After vacuum drying at 80°C, the mixture is transferred to a tubular furnace, and heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 6 hours, and naturally cooled to room temperature to obtain a lithium iron phosphate positive electrode material; wherein the mass ratio of zinc acetate to cerium oxide is 1:2, and the mass ratio of the total mass of zinc acetate and cerium oxide to the lithium iron phosphate precursor is 0.01:1; the specific conditions of ball milling are: the rotation speed is 500rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1.
[0044] Comparative Example 4
[0045] In this comparative example, no additives are used, and the method is as follows:
[0046] Step 1, ball-mill anhydrous iron phosphate, lithium carbonate and glucose for 5 hours, transfer to a tube furnace after vacuum drying at 80°C, heat to 400°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep warm for 4 hours, and naturally cool to room temperature to obtain a lithium iron phosphate precursor; wherein the molar ratio of iron to lithium is 1:1.1, and the mass ratio of the total mass of anhydrous iron phosphate and lithium carbonate to glucose is 1:0.1; the specific conditions of ball milling are: the rotation speed is 300rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1;
[0047] Step 2: The lithium iron phosphate precursor and graphene obtained in step 1 are mixed in a mass ratio of 1:0.1 and ball-milled for 3 hours. After vacuum drying at 80°C, the mixture is transferred to a tubular furnace, heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 6 hours. The mixture is naturally cooled to room temperature to obtain a low-temperature lithium iron phosphate positive electrode material. The specific conditions for ball milling are as follows: the rotation speed is 500 rpm, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 1:0.5, the grinding balls are zirconia balls, and the ball-to-material ratio is 10:1.
[0048] Comparative Example 5
[0049] In this comparative example, polyvinyl pyrrolidone is not used in step 2, and the remaining steps are the same as those in Example 1.
[0050] Electrochemical test: Weigh 0.5g of low-temperature lithium iron phosphate positive electrode material, acetylene black and polyvinylidene fluoride in a mass ratio of 85:10:5 and mix them thoroughly with an appropriate amount of N-methylpyrrolidone to form a uniform slurry, which is coated on aluminum foil and dried to form a positive electrode plate; the metal lithium sheet is used as the negative electrode; the diaphragm is an imported polypropylene microporous membrane (Celgard 2400); the electrolyte is an equal mixture of 1mol / LLiPF6, ethylene carbonate (EC) and dimethyl carbonate (DMC), and assembled into a 2025 button battery in an argon-filled glove box. The discharge capacity of Examples 1 to 3 and Comparative Examples 1 to 5 at 25°C and 0.2C rate and the discharge capacity at -20°C and 0.2C rate are obtained by testing, and the -20°C discharge capacity retention rate is calculated, as shown in Table 1, and the -20°C discharge capacity retention rate calculation formula is as follows:
[0051] -20℃ discharge capacity retention rate = 0.2C discharge capacity at -20℃ / 0.2C discharge capacity at 25℃×100%
[0052] Table 1
[0053] 25℃, 0.2C discharge capacity (mAh / g) -20℃ discharge capacity retention rate (%) Example 1 170.6 90 Example 2 167.2 87 Example 3 166.8 85 Comparative Example 1 162.5 80 Comparative Example 2 163.7 80 Comparative Example 3 160.5 78 Comparative Example 4 152.4 72 Comparative Example 5 165.3 84
[0054] As shown in Table 1, the 0.2C discharge specific capacity and -20°C discharge capacity retention rate of Examples 1 to 3 are higher than those of Comparative Examples 1 to 5, indicating that the method of the present invention can effectively improve the electrochemical properties of lithium iron phosphate materials and improve their low-temperature performance.
[0055] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A method for preparing a low-temperature lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1: Mix anhydrous iron phosphate, lithium carbonate and an organic carbon source, ball-mill, dry, and sinter for the first time to obtain a lithium iron phosphate precursor; Step 2, adding ethylenediaminetetraacetic acid and ammonia water to deionized water, stirring evenly, then adding zinc acetate, cerium oxide and polyvinyl pyrrolidone, ultrasonic treatment, concentration and drying, grinding the obtained product and performing heat treatment to obtain an additive; wherein the molar ratio of ethylenediaminetetraacetic acid, NH3·H2O and zinc acetate is 1:4~6:0.5~1; the molar volume ratio of ethylenediaminetetraacetic acid and deionized water is 1mol:0.7~1.5L; the mass ratio of zinc acetate, cerium oxide and polyvinyl pyrrolidone is 1:1~3:0.1~0.3; the concentration of ammonia water is 20wt%~30wt%; Step 3: The lithium iron phosphate precursor obtained in step 1 and the inorganic carbon source are mixed and ball-milled, and then the additive obtained in step 2 is added, and the ball-milling is continued, dried, and sintered for the second time to obtain a low-temperature lithium iron phosphate positive electrode material.
2. The method for preparing a low-temperature lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1, anhydrous ferric phosphate and lithium carbonate are mixed in a molar ratio of Fe to Li of 1:1.0-1.2; The mass ratio of the total mass of anhydrous ferric phosphate and lithium carbonate to the mass of the organic carbon source is 1:0.05~0.
2.
3. The method for preparing a low-temperature lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1, the organic carbon source is one or more of glucose, sucrose, starch, cyclodextrin, polyethylene glycol, and polyvinyl alcohol; the process parameters of the first sintering are: temperature 400-700°C, heating rate 3-10°C / min, and time 3-6h.
4. The method for preparing a low-temperature lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 2, the process parameters of the ultrasonic treatment are: power 200-400 W, frequency 50-70 kHz, time 0.5-2 h; the process parameters of the heat treatment are: temperature 400-500° C., heating rate 10-30° C. / min, time 2-4 h.
5. The method for preparing a low-temperature lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 3, the mass ratio of the lithium iron phosphate precursor to the inorganic carbon source is 1:0.05-0.2; the mass ratio of the additive to the lithium iron phosphate precursor is 0.005-0.02:
1.
6. The method for preparing a low-temperature lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step three, the inorganic carbon source is one or more of carbon black, acetylene black, graphene, and carbon nanotubes; the process parameters of the second sintering are: temperature 500-800°C, heating rate 3-10°C / min, and time 4-8h.
7. The method for preparing a low-temperature lithium iron phosphate positive electrode material according to claim 1, characterized in that: The specific conditions of the ball milling are: a rotation speed of 100-500 rpm, anhydrous ethanol as the ball milling medium, a solid-liquid ratio of 1:0.3-1, zirconia balls as the grinding balls, a ball-to-material ratio of 8-15:1, and a time of 2-6 hours.
8. A low-temperature lithium iron phosphate positive electrode material, characterized in that: The low-temperature lithium iron phosphate positive electrode material is prepared by the preparation method of any one of claims 1 to 7.
9. A battery, characterized in that: The positive electrode material of the battery is the low-temperature lithium iron phosphate positive electrode material as described in claim 8.
Citation Information
Patent Citations
Multi-metal doped lithium iron phosphate / carbon composite material and preparation method thereof
CN108511700A
Preparation method of nano-carbon coated composite lithium iron phosphate low-temperature positive electrode material
CN113113583A